Development of E-Modules to Improve the Learning Outcomes of Grade IV Students in Elementary Schools - Yanti Nipus; Fetri Yeni; Jasirial; Zuwirna (Postgraduate, University of Mataram, 2025)
This research aims to develop a valid, practical, and effective E-Module for mathematics learning for grade IV elementary school as a solution to increase the involvement of students who are less active due to less interesting teaching modules and the use of technology that is not optimal. This research uses a Research and Development (R&D) approach with a 4-D model, which consists of four stages: Define, Design, Develop, and Disseminate. Validation was carried out by four experts, namely experts in instruments, media, materials, and languages. The practicality test was carried out in two stages: trial I with two students and trial II with one educator and 12 students. The results of the study showed that the developed E-Modules had excellent validity, with the validity scores of media, materials, and language reaching 100%, 94%, and 81%, respectively. The practicality of the E-Module is also proven by the test results which show a percentage of 99.5% in trial I and 95.6% in trial II. In addition, students provided an average practicality of 99.1%. The level of effectiveness of the E-Module is reflected in the results of the pretest and posttest, where the average score of students increased from 65 in the pretest to 89.17 in the posttest, with an N-Gain score of 0.67 which indicates a significant increase in learning outcomes. Based on these results, the E-Module in the mathematics subject of grade IV elementary school can be declared valid, practical, and effective to be used in learning.